Perbedaan karakteristik pasien kasus gigitan hewan penular rabies di Puskesmas Kuta Utara periode Agustus – Oktober tahun 2021 - Desak Ayu Dhyana Nitha Dewi; Putu Ayu Swandewi Astuti; I Gusti Agung Alit Naya (DiscoverSys Inc., 2022)
Background: The bite of an animal that transmits rabies is still a problem in Indonesia, one of which is in the province of Bali. The high dog population and the habit of straying dogs cause the risk of rabies transmission due to dog bites to be higher. North Kuta District is one of the areas where the case of bites of animals that transmit rabies is found. The purpose of this study was to determine the differences in the characteristics of patients with rabies-transmitting animal bites at the North Kuta Health Center from August to October 2021. Methods: The study used a quantitative analytical design with a cross-sectional approach. The sample is patient medical record data at the North Kuta Health Center for the period August to October 2019. Data analysis was carried out using descriptive tests to describe patient characteristics. Bivariate test using Chi-square or Fisher’s Exact test was carried out to determine the differences in the characteristics of patients bitten by rabies-transmitting animals who received the Anti Rabies Vaccine (VAR) with a p value of <0.05 showing a significant value. Results: There were 96 patients with rabies-transmitting animal bites at the North Kuta Health Center for the period August – October 2019. The characteristics of the patients showed that most of them were 20 years old (37.50%), bitten by a stray dog (70.83%), the condition of the animal when it was found. still alive (68.75%), bitten on the right leg (37.50%), and received VAR (52.08%). The highest cases of animal bites that transmit rabies occurred during the month of October (41.67%). The results of the Chi-square test showed that the amount of VAR administration was significantly different based on the characteristics of the biting animal species (p<0.0001) and the animal's condition (p<0.0001). Conclusion: There are still cases of animal bites that transmit rabies in North Kuta District. There was a significant difference in the amount of VAR administration based on the characteristics of the biting animal species and the animal's condition. Latar Belakang: Gigitan hewan penular rabies masih menjadi permasalahan di Indonesia, salah satunya di Provinsi Bali. Populasi anjing yang tinggi serta kebiasaan meliarkan anjing menyebabkan risiko penularan rabies akibat gigitan anjing menjadi semakin tinggi. Kecamatan Kuta Utara merupakan salah satu daerah ditemukannya kasus gigitan hewan penular rabies. Tujuan penelitian ini mengetahui perbedaan karakteristik pasien kasus gigitan hewan penular rabies di Puskesmas Kuta Utara periode Agustus hingga Oktober 2021. Metode: Penelitian menggunakan rancangan kuantitatif analitik dengan pendekatan potong lintang. Sampel merupakan data rekam medis pasien di Puskesmas Kuta Utara periode Agustus hingga Oktober 2019. Analisis data dilakukan dengan menggunakan uji deskriptif untuk menggambarkan karakteristik pasien. Uji bivariate menggunakan Chi-square atau Fisher’s Exact test dilakukan untuk mengetahui perbedaan karakteristik pasien gigitan hewan penular rabies yang memperoleh Vaksin Anti Rabies (VAR) dengan nilai p<0,05 menunjukan nilai signifikan Hasil: Terdapat 96 pasien kasus gigitan hewan penular rabies di Puskesmas Kuta Utara periode Agustus – Oktober 2019. Gambaran karakteristik pasien memperlihatkan sebagian besar berusia ≤20 tahun (37,50%), digigit oleh anjing liar (70,83%), kondisi hewan saat ditemukan masih hidup (68,75%), digigit di kaki kanan (37,50%), dan memperoleh VAR (52,08%). Kasus gigitan hewan penular rabies tertinggi terjadi selama bulan Oktober (41,67%). Hasil uji Chi-square menunjukkan bahwa jumlah pemberian VAR berbeda signifikan berdasarkan karakteristik jenis hewan penggigit (p<0,0001) dan kondisi hewan (p<0,0001). Kesimpulan: Masih terdapat kasus gigitan hewan penular rabies di Kecamatan Kuta Utara. Terdapat perbedaan bermakna jumlah pemberian VAR berdasarkan karakteristik jenis hewan penggigit dan kondisi hewan.